Left ventricular strain derived from cardiac magnetic resonance can predict outcomes of pulmonary valve replacement in patients with repaired tetralogy of Fallot - Zhuang, Baiyan; Yu, Shiqin; Feng, Zicong; He, Fengpu; Jiang, Yong; Zhao, Shihua; Lu, Minjie; Li, Shoujun (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Several adults with repaired tetralogy of Fallot (rToF) undergo pulmonary valve replacement (PVR) to reduce the right ventricular volume and retain right ventricular function. However, there is currently no consensus on the ideal time for PVR surgery in asymptomatic patients with rTOF with pulmonary regurgitation (PR). Clinical outcomes after PVR are also indeterminate. Recently, myocardial strain and strain rate derived from cardiac magnetic resonance (CMR) feature tracking were found to be more sensitive to right ventricular dysfunction than conventional parameters and therefore may add prognostic value in patients with rToF. We aimed to analyze whether pre-PVR left ventricular (LV) strain and strain rate detected by CMR feature tracking are associated with midterm outcomes after PVR in patients with rToF. Methods: Seventy-eight asymptomatic patients with rToF who required PVR due to moderate or severe PR were prospectively enrolled between January 2014 and June 2020. CMR cine sequences were obtained, and feature tracking parameters were measured preoperatively. Adverse events were documented during the follow-up. Receiver operating characteristic analysis was performed to determine the cutoff value. Kaplan–Meier curves were drawn with log-rank statistics; moreover, univariate and multivariate Cox proportional hazards regression analyses and Harrel C-indices were analyzed. Results: During 3.6±1.8 years of follow-up, 25 adverse events were recorded. Kaplan–Meier survival curves and univariate Cox analysis verified that patients with significantly reduced radial strain (RS), circumferential strain (CS), longitudinal strain (LS), RS rate at systole and diastole (RSRs and RSRe), and circumferential and LS rates at diastole (CSRe and LSRe) had worse event-free survival. After multivariate correction, only LS and LSRe remained significantly associated with adverse outcomes (hazard ratio=1.243 [1.083–1.428] and 0.067 [0.017–0.258], respectively, all p<0.05). The cutoff values of LS and LSRe were −12.30(%) and 1.07(s-1), respectively. Conclusion: The LV strain and strain rate prior to PVR are important prognostic factors for adverse events after PVR in rToF.